2018
DOI: 10.2196/10175
|View full text |Cite
|
Sign up to set email alerts
|

Proposing a Transactional Model of eHealth Literacy: Concept Analysis

Abstract: BackgroundElectronic health (eHealth) literacy was conceptualized in 2006 as the ability of internet users to locate, evaluate, and act upon web-based health information. Now, advances in eHealth technology have cultivated transactional opportunities for patients to access, share, and monitor health information. However, empirical evidence shows that existing models and measures of eHealth literacy have limited theoretical underpinnings that reflect the transactional capabilities of eHealth. This paper describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
119
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(131 citation statements)
references
References 49 publications
2
119
0
10
Order By: Relevance
“…Though the original instrument showed high correlations with related concepts, more recent studies have indicated a weaker correlation between the eHEALS and Internet use (van der Vaart et al, 2011) and traditional health literacy (Quinn, Bond & Nugent, 2017). Paige et al (2018) also point out that the eHEALS is intended to reflect the Lily Model but the items in the instrument are not reflective of the model's competencies. In addition to this, Zrubka et al (2019) describe eHEALS as a "selfefficacy-related measure" because of the focus on self-assessment.…”
Section: F Health Literacymentioning
confidence: 96%
See 4 more Smart Citations
“…Though the original instrument showed high correlations with related concepts, more recent studies have indicated a weaker correlation between the eHEALS and Internet use (van der Vaart et al, 2011) and traditional health literacy (Quinn, Bond & Nugent, 2017). Paige et al (2018) also point out that the eHEALS is intended to reflect the Lily Model but the items in the instrument are not reflective of the model's competencies. In addition to this, Zrubka et al (2019) describe eHEALS as a "selfefficacy-related measure" because of the focus on self-assessment.…”
Section: F Health Literacymentioning
confidence: 96%
“…The researchers examine eHealth literacy from a communication perspective and emphasise the importance of the transactional component to eHealth literacy. Paige et al (2018) began with a systematic review of literature on eHealth literacy models. As a result of the systematic review of literature, the researchers redefined eHealth literacy as "the ability to locate, understand, exchange, and evaluate health information from the Internet in the presence of dynamic contextual factors, and to apply the knowledge gained across ecological levels for the purposes of maintaining or improving health".…”
Section: The Transactional Ehealth Literacy Instrument (Tehli)mentioning
confidence: 99%
See 3 more Smart Citations